2016
DOI: 10.5194/nhess-16-1369-2016
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and drought effects on rural income distribution in the Mediterranean: a case study for Spain

Abstract: Abstract. This paper examines the effects of climate change and drought on agricultural incomes in Spanish rural areas. Present research has focused on the effects of these extreme climatological events through response functions, considering effects on crop productivity and average incomes. Among the impacts of droughts, we focused on potential effects on income distribution. The study of the effects on abnormally dry periods is therefore needed in order to perform an analysis of diverse social aspects in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Moreover, Quiroga and Suárez (2016) reported that higher temperature and lower precipitation also negatively affect agricultural income distribution in Spain. Results of studies in Ethiopia are also similar (Deressa, 2007; Aragie, 2013; Gebreegziabher et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Quiroga and Suárez (2016) reported that higher temperature and lower precipitation also negatively affect agricultural income distribution in Spain. Results of studies in Ethiopia are also similar (Deressa, 2007; Aragie, 2013; Gebreegziabher et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Multisectoral drought impact assessments have shown the value of interlinking natural and socio-economic consequences. Examples include Eklund and Seaquist ( 2015 ) on the full impact cascade of drought in Iraqi Kurdistan, Quiroga and Suarez ( 2016 ) on income distribution shifts in Spain, Carse ( 2017 ) on supply issues at the Panama Canal during the 2015–2016 drought, Vicente-Serrano et al ( 2021 ) on vegetation and agriculture in a Spanish basin and the review of Wlostowski et al ( 2022 ) on nonagricultural socio-economic sectors in the Western US. For Europe, Ionita et al ( 2017 ) assessed the 2015 drought mainly affecting Eastern Central Europe and Southern Germany in detail using meteorological fields, while prominent multisectoral impacts have been addressed by Van Lanen et al ( 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most vulnerable plants, under extreme drought conditions, are those slow to adapt -like perennial fruit trees [6]. One of the most important perennial crops at risk in the Mediterranean region is the olive tree [7] (Olea Europea L.), which is native to the Mediterranean basin that has considerable socio-economic importance. Olive is cultivated in rainfall conditions due to its minimal requirements in water [8].…”
Section: Introductionmentioning
confidence: 99%